Polynomial Division and Factorization - Reducing a Polynomial -
Given that x=1 is a zero of f(x), show that f(x) = x3 -
4x2 + 2x + 1 may be factored as
using a procedure
nearly identical to that used in Exercise 5. Note that in this case,
you will need to use the Quadratic Formula to find the zeros of the
quadratic. The justification has been given - no further
justification is needed.
| x=1 is a zero of f(x) = x3
- 4x2 + 2x + 1
Synthetic Division, Properties of Zeros, the Zero Product Rule,
and the Quadratic Formula.